Flora of New Forest, Dehra Dun with Special Reference to Indigenous Species - Balapure, K. M. (Indian Forester, 1959)
This paper gives an account of the indigenous flora of New Forest, Dehra Dun. In all 56 families of flowering plants and 275 species have been dealt with. Ferns and mosses found in shady moist localities have been excluded. Bentham and Hooker’s system of classification has been followed in arranging the families. Along with a short description of the plants, their period of flowering has been given. An attention has been drawn to a large number of exotic plants that are getting naturalized in the estate.